Impact of Human Development Index (HDI) and Labor Participation on Poverty in North Sumatra Province for the Period 2010-2023 - Tasya G Sianturi; Graciela Br Sembiring; Melody Sitorus; Syaqinah Ujung (Outline Publisher, 2025)
Poverty is a multidimensional issue that is still a serious challenge in development in North Sumatra Province. This study aims to analyze the effect of the Human Development Index (HDI) and Labor Participation on the poverty rate during the period 2010–2023. HDI is used as an indicator of quality of life through the dimensions of education, health, and standard of living, while Labor Participation reflects the involvement of the working-age population in economic activities. Secondary data used were obtained from the Central Statistics Agency (BPS). The analysis was carried out using multiple linear regression with the Ordinary Least Squares (OLS) approach and supported by classical assumption tests such as normality, multicollinearity, autocorrelation, and heteroscedasticity. The results of the study indicate that HDI has a negative and significant effect on the poverty rate, while labor participation does not have a significant effect partially. However, simultaneously, both variables jointly affect poverty in North Sumatra. This finding emphasizes the importance of inclusive human development policies and the creation of quality jobs to accelerate poverty alleviation.